Factors of loan portfolio quality on the profitability of a municipal savings and loan institution - Cueto Sanchez, Sandra Cristina (2021)
The quality of the loan portfolio in the profitability of the Caja Municipal de Ahorro y Crédito De Tacna S.A. The type of investigation was basic; the design was non-experimental, longitudinal; the level was causal - explanatory; The sample consisted of the historical documents of the Caja Municipal de Ahorro y Crédito De Tacna S.A. issued by the SBS, for the period 2017 - 2018, which contained information about the entity's internal variables, in addition to the historical documents issued INEI, about macroeconomic variables; Descriptive and inferential statistics were found for the evaluation of the variables. Among the most outstanding results, it was obtained that profitability started very close to 0% at the beginning of the 2017 period, rising until December of the 2017 period and falling sharply; This trend was similar at the beginning and end of the 2018 period. A linear regression could not be performed, but there is still the possibility of applying a multivariate regression that allows the variables to be grouped within a model. If a model is developed by removing some variables, the contribution of the model would not be substantial. However, it is possible to affirm that there is a high influence of Placements by type of credit on the Profitability of the Caja Municipal de Ahorro y Crédito De Tacna S.A. with an average coefficient of determination (r2) of 0.6133.